(untitled) (Bangladesh Critical Care Journal, 2022)
Background: In the recent years, the prevalence of chronic kidney disease (CKD) has increased in the community. CKD has been associated with several cardiac diseases. The aim of the study was to assess the cardiac status of the CKD patients. Methods: This cross-sectional study was done in Rangpur Medical College Hospital, Rangpur from June 2013 to November 2013. A total of 50 CKD patients were selected by convenient type of sampling. An informed written consent was taken before enrolling the patients into the study. All the data were recorded in a pre-structured questionnaire. Analysis of the data was done by SPSS V.22. A P value of <0.05 was considered as significant. Results: A total of 50 cases were studied; age ranging from 23 years to 75 years and the mean age ± SD was 45.8 ± 11.56. We study showed that 30% of patients had cardiac dysfunction, among them 18% had systolic dysfunction and 12% had diastolic dysfunction. In the study, among the diastolic dysfunction 10% had slow relaxation pattern and 02% had restrictive pattern of diastolic dysfunction. In our study, we have seen that 36% patients had left ventricular hypertrophy. ECG findings showed that 36% of patients had LVH, 6% showed anterolateral ischaemia, 6% showed inferior ischaemia, 4% showed sinus bradycardia, 2% sinus tachycardia, 2% anterior ischaemia and 2% septal ischaemia. In our study chest X-ray P/A view showed 30% had cardiomegaly, 4% had pulmonary oedema, 4% had pleural effusion and 62% had normal findings. When we staged the CKD with the GFR, it was shown that 90% patients had GFR <15, 6% had GFR in between 30—59 and 4% had in between 15-29ml/min. Systolic dysfunction was more (8%) in patients having GFR < 15, whereas it was only 1% in patients having GFR in between 30—59. Conclusion: This study an suggested association between chronic kidney disease (CKD) and cardiac dysfunction, both systolic and diastolic. It demonstrated a high prevalence left ventricular hypertrophy (LVH) as well. Early detection and treatment of causes of CKD should be pursued aggressively at the earliest possible time to prevent cardiovascular complications and thus reduce morbidity. Bangladesh Crit Care J September 2022; 10(2): 99-103